The Role of Perceived Risk in Engaging Customer and Employees for Value Creation in Services - Ritu Srivastava; Diptiman Banerji
Value creation, customer engagement and employee engagement have emerged as important organizational outcomes for continued success. At the turn of the new decade, it is imperative to identify new research directions for these outcomes to improve the marketing effectiveness of organizations while keeping people at the centre of this pursuit. The present study is propelled by this motivation. The study started with the exploration of the relationship of customer and employee engagement in value creation, while limiting the scope to services. The extant literature has not studied the three together. The second phase of the study dwelled on identifying common links among the three to develop a conceptual model that brought the concepts of customer engagement, employee engagement and value creation together. Perceived risk was identified as the underlying phenomenon that connected all three to be part of a social system. A conceptual framework has been proposed for connecting perceived risk to customer engagement and employee engagement that would create value in service organizations. The study identifies future research directions for theory building and practice